In Search of Architectural Patterns for Software Security. - Ryoo, Jungwoo; Laplante, Phil; Kazman, Rick (Computer (00189162), 2009)
The article provides a rationale and a description to identify both secure and unsecure software architectures in an effort to uncover architectural styles that are either resilient or vulnerable to security attacks. It focuses on architectural constructs and properties that render software more secure, regardless of its size or purpose, and how it will remain secure as new threats emerge. The article also seeks to determine which architectural constructs and properties might make software less secure.